128k views
3 votes
All you need is in the photo I DON'T WANT STEP BY STEP ANSWER FAST please fdsd

All you need is in the photo I DON'T WANT STEP BY STEP ANSWER FAST please fdsd-example-1

1 Answer

3 votes

We have the following:


\begin{gathered} x=\frac{-b\pm\sqrt[]{b^2-4ac}}{2a} \\ a=5 \\ b=0 \\ c=-80 \end{gathered}

replacing:


\begin{gathered} x=\frac{-0\pm\sqrt[]{0^2-4\cdot5\cdot-80}}{2\cdot5}=\frac{\pm\sqrt[]{1600}}{10}=(\pm40)/(10)=\pm4 \\ x_1=4 \\ x_2=-4 \end{gathered}

User Ganesh Kalje
by
5.5k points